Sistem Informasi Penjualan Sepeda Motor Bekas Menggunakan Algoritma C4.5 - Wimmie Handiwidjojo1; Ferry Kristian Sukendro (Universitas Ciputra Surabaya, 2015)
The motorcycle as transportation vehicles have a fairly high number compared to other transportation vehicles. A lot of motorcycles are manufactured with a variety of brands, types, color, etc. No wonder, the motorcycle shop owners tend to be confused determining the attributes of motorcycles such as brand, type, color and production year which meet the market demand. To solve the problem, we build a system that can calculate the value of the attributes of the most influential in the sale of used motorcycles based on the available data. In this research, the authors used C4.5 algorithms to be implemented into the system. This system will calculate the total value of the gain of each attribute on motorcycle sales data. This research resulted a system that can record sales and purchases transactions to be used in the calculation of the gain of each attribute of motorcycle using C4.5 algorithms. The output of this system will show the value of the gain of each attribute (brand, type, color and production year). The highest position of the attribute means the highest value of the gain that also means it meets the market demand.